INTERFERENSI BAHASA BUGIS TERHADAP PENGGUNAAN BAHASA INDONESIA DI PASAR TRADISIONAL DESA SIOYONG KABUPATEN DONGGALA - Saharuddin, Saharuddin (BAHASANTODEA, 2016)
The title of this research â€œThe InterferenceÂ  of Buginese to the using Indonesian Language In the Sioyong Traditioal Market Donggala Regencyâ€, the problem of this reearch is (1). How is the Buginese Interference form to the using indonesian language in the sioyong traditional market of Donggala regency, (2). What are the cause interference of buginese factors to the using indonesian language in the sioyong traditional market donggala regency happen. The purpose of this research are : (1) To describe the cause interference of buginese factors to the using indonesian language in the Sioyong traditional market donggala regency happen. The data accumulation was done by some of the techniques. There are: (1) Observation, (2) Interview, (3) Documentation, and (4) Fieldwork notes. There are two sources data. They are primary and secondary data. The method that used in this analysis data is descriptive qualitative method and the data analysis technique was done by (1) Data Accumulation, (2) Data reduction, (3) Data presentation steps (4) concluding step. According of this research could take the some of concludes: the interference happening at : (1). Phonology Interference is the changes of phonem /o/ to be /u/, Phonemes /e/ be /i/, the missing of Phoneme /e/, /h/ and /k/ (2). Morphology interference, (a) affixation interference; is the prefix {pem-} be {pen-}, {pe-} be {pa-}, {ter-} be {ta-}, the using of enclitic {-pi}and {-kik}, and (b) lexical Interference are verb interference, noun interference, adjective interference, question word interference, and numeral word interference. (3) Syntactic interference is the changes of the structure sentence pattern of indonesian language which interferenced by buginese. There are (a) Phrase interference, and (b) Clause Interference.